Generation and Characterisation of Human Mesenchymal Stem Cells from Human Umbilical Cord - Tong, Chih Kong (2010)
Mesenchymal stem cells (MSC) are multipotent stem cells that possess the ability to self-renew, capable of differentiating into mesodermal lineage and exert an immunomodulatory activity. These qualities grant MSC great potential in regenerative medicine, immunotherapy and gene therapy. The increasing demand of tissue regeneration and allogenic transplantation necessitate the need for a readily available source of MSC as an ‘off-the-shelf’ product for quick and effective treatment. To date, MSC can be generated from human umbilical cord which was once considered clinical waste. The aim of this study is to establish an optimal method to generate and characterise MSC from human umbilical cord samples. In this study, a novel generation method by combining mild enzymatic digestion and mechanical dissociation is established. Briefly, the outer layer of umbilical cord is separated from the blood vessels and remnant cord blood prior to processing. The umbilical cord samples are subjected to explants culture, enzymatic degradation or a combination of enzymatic and mechanical dissociation to obtain a single cell suspension for the generation of umbilical cord MSC (UC-MSC). Once UC-MSC expand, they are characterised by immunophenotyping and differentiation assays. The data show that UC-MSC express common MSC surface markers (CD105+, CD73+, CD29+, CD90+, CD34-, CD45-, MHC class I+, MHC class II-, CD80-,CD86-) and are capable of differentiating into osteoblasts and adipocytes. Simultaneously, the properties of UC-MSC are evaluated in the presence and absence of basic fibroblast growth factor (bFGF). The results show that bFGF supplementation significantly affects the morphology, growth kinetics, cell cycle and cellular functions of UC-MSC. Furthermore, bFGF enhances the growth rate of UCMSC by reducing the doubling time (about 3-4 fold) and skews the cytokine secretion profile (decreases MMP3 and VEGF production). Similar to bone marrow MSC, UC-MSC also exert an immunomodulatory effect on T cells. In the presence of UC-MSC, T cell activation is preserved. However their proliferation is profoundly inhibited in a dose-dependent manner. T cells are arrested anergy in G0 phase of the cell cycle and this inhibitory activity requires cell-to-cell contact. This study reveals that UC-MSC share similar characteristics with BM-MSC and potentially serve as a future source of MSC for clinical use.